The Value of Integrity in the Reports of Work - Simona-Roxana Ulman (CES Working Papers, 2015)
The most important aim of this paper is to identify the main general ethical values conducting to personal integrity, to build the general ethical values pyramid and, so, helping to improve the reports of labor for having positive results on the economic field. In this context, the human psychological development theory thorough by Maslow is exploited as example for the building of a human values hierarchy necessary to the individual as a social being to engage in normal interactions with the others. These general values are an imperative for the person's integration in society, also contributing to his belonging society's welfare and to its performance.
Keywords: A14; 330; ethical values; reports of work